IMPLEMENTATION OF THE TEACHER CODE OF ETHICS IN BUILDING STUDENT CHARACTER AT SDN BUGIH 3 PAMEKASAN: INTEGRITY AND EXEMPLARY PERSPECTIVE - Sofia Ningsih; Gita Puspita Sari; Maria Ulfa; Aldiky Rachman Firdausi; Abd. Mukhid; Wurrotul Kamila (STAI Asy-Syukriyyah, 2026)
This qualitative case study examines how the Teacher’s Code of Ethics shapes student character development at SDN Bugih 3 Pamekasan, focusing on Islamic Education teachers’ internalization of professional values. Data were collected via in-depth interviews with experienced teachers (8–10 years). Findings indicate that the code is implemented not as mere administrative compliance, but as a compassion-based authority and a “living curriculum” rooted in Uswatun Hasanah. Consistent alignment between teachers’ words and actions fosters student trust, shifting compliance from fear-driven obedience to autonomous moral awareness and reducing bullying. However, heavy administrative workloads and inconsistent home parenting styles hinder sustained character transformation. Consequently, this study recommends developing an integrated character ecosystem through strategic school–parent collaboration and optimizing teacher psychological well-being to maintain ethical exemplarity.